Pluripotent Stem Cells Derived From Mouse and Human White Mature Adipocytes. (6th January 2014) - Jumabay, Medet; Abdmaulen, Raushan; Ly, Albert; Cubberly, Mark R.; Shahmirian, Laurine J.; Heydarkhan-Hagvall, Sepideh; Dumesic, Daniel A.; Yao, Yucheng; Boström, Kristina I.
Abstract : This study defined the stem cell characteristics of dedifferentiated fat (DFAT) cells as they are generated from adipocytes and the relationship between these characteristics and lineage differentiation. Results suggest that adipocyte-derived dedifferentiated fat cells represent a plastic stem cell population that is highly responsive to changes in culture conditions and may benefit cell-based therapies. Abstract: White mature adipocytes give rise to so-called dedifferentiated fat (DFAT) cells that spontaneously undergo multilineage differentiation. In this study, we defined stem cell characteristics of DFAT cells as they are generated from adipocytes and the relationship between these characteristics and lineage differentiation. Both mouse and human DFAT cells, prepared from adipose tissue and lipoaspirate, respectively, showed evidence of pluripotency, with a maximum 5–7 days after adipocyte isolation. The DFAT cells spontaneously formed clusters in culture, which transiently expressed multiple stem cell markers, including stage-specific embryonic antigens, and Sca-1 (mouse) and CD105 (human), as determined by real-time polymerase chain reaction, fluorescence-activated cell sorting, and immunostaining. As the stem cell markers decreased, markers characteristic of the three germ layers and specific lineage differentiation, such as α-fetoprotein (endoderm, hepatic), Neurofilament-66 (ectoderm, neurogenic), and Troponin I (mesoderm, cardiomyogenic), increased. However, no teratoma formation was detected after injection in immunodeficient mice. A novel modification of the adipocyte isolation aimed at ensuring the initial purity of the adipocytes and avoiding ceiling culture allowed isolation of DFAT cells with pluripotent characteristics. Thus, the adipocyte-derived DFAT cells represent a plastic stem cell population that is highly responsive to changes in culture conditions and may benefit cell-based therapies.